The comparison of larvacidal effects of ethanol extract of cinnamon (Cinnamomum burmanni) and temephos against Aedes aegypti mosquitoes - Edra, Alven; Maryanti, Esy; Nugraha, Dimas P (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by Dengue Virus through Aedes aegypti mosquito vector with rapid deployment and be able to cause death.. The use of chemical insecticides to suppress cases in the comunity when used continuously for a long time have a detrimental impact, because of that it is necessary to find an alternative way wich is form of botanical larvacides, such as cinnamon bark (Cinnamomum burmanni). The aim of this research was to find out the comparison of larvacidal effects of ethanol extracts of cinnamon and temephos against Aedes aegypti mosquito larvae. This was the experimental research with three repetitions that each concentration was containing 10 larvae. The analysis of research result use the analysis regresi probit wich was gotten LC50 was 85,727 ppm, LC90 was 135,180 ppm, LC99 was 175,497 ppm and temephos with 1 ppm concentration kills 100% larva. It can be concluded that temephos was better than the extract of cinnamon as larvacide.Keywords: larvacidal effects, Cinnamomum burmanni, Aedes aegypti, temephos